Club Licencing Regulations (CLR) on Infrastructure Aspect in PSSI Bandung and Persib Bandung Football Club: An Evaluation Study - Lukman Widjayana; Moch Asmawi; James Tangkudung; Anggi Setia Lengkana (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2022)
This study aims to evaluate infrastructure aspects hated on the Club Licensing Regulation (CLR) of the City Association (Askot) of the All Indonesian Football  Association (PSSI) and the Persib Bandung Football Club (Persib), as well as the effectiveness of in improving the performance of both: Askot and the Persib Bandung. This research is an evaluative study with a Context, Input, Process rind Product (CIPP) review. It has relevance value because of its holistic approach to evaluation to provide a very detailed and broad picture of a program, from its context to the implementation process. Context stages include goals and objectives, legal law and policies, legality, and determination of organizational structure. Input stages include stadium eligibility, control room availability, capacity, first-aid availability, doping control room, field specifications, press and media facilities, audience seats, and supporting accommodation. The process stages include basic rules, operating procedures, facility use, maintenance, and monitoring. The product stages include physical fitness, athlete skills, and club achievement. The process reaches 30.0% in the "very low" category as well as the Product (33.3%). The overall evaluation of the infrastructure aspects based on the CLR on the PSSI Bandung and Persib was 41.50% (very low). Based on the results of a comprehensive evaluation, it is stated that a blueprint to manage the overall objectives and stadium maintenance is needed. It is also needed to overcome the obstacles during the process. It is necessary to lobby for the authority to manage the stadium independently to improve players' physical fitness and skills further because an advanced and sophisticated infrastructure supports it.